2018
DOI: 10.3389/fncel.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Expression in Perineuronal Nets After Goldfish Spinal Cord Lesion

Abstract: Perineuronal nets (PNNs) surrounding neuronal cell bodies regulate neuronal plasticity during development, but their roles in regeneration are unclear. In the PNNs, chondroitin sulfate (CS) is assumed to be involved in inhibiting contact formation. Here, we examined CS expression in PNNs in the ventral horn of a goldfish hemisected spinal cord in which descending axons regenerate beyond the lesion to connect with distal spinal neurons. In intact fish, chondroitin sulfate A (CS-A)–positive PNNs accounted for 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Prior studies have already described changes in PNN remodeling following SCI in WT mice [11,25,26]. In agreement with our previous results analyzing the changes in PNN structure after a thoracic cord contusion [11], we observed reduced PNN thickness around disconnected lumbar motoneurons.…”
Section: Remodeling Of Spinal Perineuronal Nets After Spinal Cord Injurysupporting
confidence: 93%
“…Prior studies have already described changes in PNN remodeling following SCI in WT mice [11,25,26]. In agreement with our previous results analyzing the changes in PNN structure after a thoracic cord contusion [11], we observed reduced PNN thickness around disconnected lumbar motoneurons.…”
Section: Remodeling Of Spinal Perineuronal Nets After Spinal Cord Injurysupporting
confidence: 93%
“…Reduced staining of aggrecan around lumbar MN was reported 35 days after a thoracic SCI, recovering normal levels at later stages (Sánchez-Ventura et al, 2020 ). Similar findings were described after hemisection in goldfish (Takeda et al, 2018 ). A study evaluating aggrecan synthesis and degradation found a significant decline in aggrecan levels after SCI too (Lemons et al, 2001 ).…”
Section: Injured Nervous System: Spinal Cord Injurysupporting
confidence: 86%
“…Perineuronal nets are specialized ECM that encapsulate the soma and the proximal dendrites of some neurons in the CNS. This mesh-like structure has been described in various mammals [e.g., rodents (Kalb and Hockfield, 1988 ; Galtrey et al, 2008 ), cats (Hockfield, 1983 ), dogs (Atoji et al, 1997 ), sheep (Härtig et al, 2017 ), primates (Mueller et al, 2016 ), and humans (Jäger et al, 2013 )] and non-mammal species [e.g., fish (Takeda et al, 2018 ), birds (Balmer et al, 2009 ), frogs (Gaál et al, 2014 ), and chickens (Morawski et al, 2009 )]. Among all of them, spinal PNNs have been characterized in fish, rodents, cats, primates, and humans.…”
Section: Perineuronal Netsmentioning
confidence: 99%
“…Previous studies revealed that the administration of ChABC after spinal cord injury removed CS-GAGs from PNNs at the lesion site, thus promoting plasticity and nerve regeneration in long tracts entering the lesion site. In goldfish with a spinal hemisection, plasticity in the spinal neurons might be restored by downregulation of CS in the PNNs in the regeneration process [ 93 ]. Moreover, the administration of ChABC degrades CSPGs in the PNNs and appears to boost the plasticity of spinal neurons and to promote the sprouting of spared long tract axons [ 94 ].…”
Section: Pnns’ Structure and Functionsmentioning
confidence: 99%